Search for bottom squark pair production in proton-proton collisions at [Formula: see text] TeV with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2016)
The result of a search for pair production of the supersymmetric partner of the Standard Model bottom quark ([Formula: see text]) is reported. The search uses 3.2 fb[Formula: see text] of pp collisions at [Formula: see text] TeV collected by the ATLAS experiment at the Large Hadron Collider in 2015. Bottom squarks are searched for in events containing large missing transverse momentum and exactly two jets identified as originating from b-quarks. No excess above the expected Standard Model background yield is observed. Exclusion limits at 95 % confidence level on the mass of the bottom squark are derived in phenomenological supersymmetric R-parity-conserving models in which the [Formula: see text] is the lightest squark and is assumed to decay exclusively via [Formula: see text], where [Formula: see text] is the lightest neutralino. The limits significantly extend previous results; bottom squark masses up to 800 (840) GeV are excluded for the [Formula: see text] mass below 360 (100) GeV whilst differences in mass above 100 GeV between the [Formula: see text] and the [Formula: see text] are excluded up to a [Formula: see text] mass of 500 GeV.